Robin Williams : comic genius [videorecording (DVD)]. - Black, Lewis, 1948-; Brownstein, Paul; Peisch, Jeffrey; Shine, Kelley (Time Life, 2018)
"Robin Williams started performing stand-up comedy in the mid-'70s and amazed audiences with his frenetic energy and believably quick wit. He skyrocketed to stardom and performed steadily for nearly four decades, entertaining audiences across the globe."--Container